P159 Peripheral Blood Mononuclear Cells from patients with Idiopathic Pulmonary Arterial Hypertension are Hyporesponsive to Inflammatory stimuli. (14th November 2013) - Price, LC; Paul-Clark, M; Meng, C; Shao, D; Mitchell, JA; Adcock, IM; Wort, SJ
Abstract : Background: Inflammation is a key feature of pulmonary arterial hypertension (PAH); circulating levels of plasma cytokines and chemokines are raised, some of which (including interleukin (IL)-6 and CXCL8) are associated with increased mortality (1). We wished to determine whether it was possible to detect an altered inflammatory phenotype in circulating inflammatory cells from PAH patients compared to controls. Methods: Following ethical approval, patients with idiopathic PAH and age-matched non-smoking control subjects were selected. Peripheral blood mononuclear cells (PBMC) (10 5 cells) or citrated whole blood (WB) were plated into 96-well plates and treated with E. Coli LPS (0–1µg/ml) (Sigma) or recombinant TNF-a (0–10ng/ml) (R&D systems) for 24h at 37°C. Following centrifugation, plasma was aspirated and samples frozen at -20°c, and IL-6 and CXCL8 ELISAs later performed. Data are mean ± SEM. Results: All patients had idiopathic PAH (n = 12) (7 in NYHA class III-IV) with 6MWD 370 ± 18m, mPAP 72 ± 5mmHg). All patients were taking advanced PAH therapies but not conventional anti-inflammatory therapies. There was no age difference between patients and controls (n = 9) (36.5 ± 3.7 vs. 36.2 ± 2.7 years, NS). At baseline, release of IL-6 and CXCL8 was higher from PBMC from PAH patients than controls (918.1 ± 280.5 vs. 195.2 ± 64.3 for IL-6 (p < 0.05) and 4203 ± 1354 vs. 1048 ± 288.4 p < 0.05 for CXCL8), although no difference was seen between groups from the whole blood assays. Following stimulation with LPS, however, release of both IL-6 and CXCL8 was lower from both WB and PBMC assays for PAH patients compared to controls. For example for LPS-induced IL-6 release from PBMC, both the maximal effect (Emax ) was lower in PAH vs. controls (5148 ± 1320 vs. 9154 ± 2510 pg/ml, p < 0.05) and the log EC50 (half maximal effective concentration) was higher in PAH vs. controls (-2.70 ± 0.27 vs. -5.90 ± 1.16 µg/ml, p < 0.01) (Figure 1 ). Similar results were seen following stimulation with TNF-a. Conclusion: The main findings of this study are that: (1) baseline CXCL8 and IL6 release was higher from PBMCs of patients with PAH compared to control donors; (2) PBMCs and WB from patients were hyporesponsive to LPS (and TNF-a), suggesting an altered inflammatory phenotype, at least in these models, to these stimuli. References: Soon E. et al, Circulation . 2010;122(9):920–7